1997
DOI: 10.1111/j.1365-2168.1997.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Duplex assessment of run-off before femorocrural reconstruction

Abstract: Duplex imaging is superior to arteriography for preoperative assessment of distal run-off for femorocrural reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…11). A technically adequate examination was reported to be feasible in 80±100 % of cases, taking into account that careful exploration of distal vessels is a time-consuming investigation (from 10 to 90 min) [10,11,41,43,46,47,48,49,50,51,52]. Caster et al reported a success rate of 94, 96 and 83 % for the anterior tibial, posterior tibial and peroneal arteries, respectively [48].…”
Section: Accuracy Of Colour Doppler In the Detection Of Stenoses And mentioning
confidence: 99%
See 1 more Smart Citation
“…11). A technically adequate examination was reported to be feasible in 80±100 % of cases, taking into account that careful exploration of distal vessels is a time-consuming investigation (from 10 to 90 min) [10,11,41,43,46,47,48,49,50,51,52]. Caster et al reported a success rate of 94, 96 and 83 % for the anterior tibial, posterior tibial and peroneal arteries, respectively [48].…”
Section: Accuracy Of Colour Doppler In the Detection Of Stenoses And mentioning
confidence: 99%
“…Doppler criteria included velocity measurements and colour images evaluating anatomical features such as calibre, calcifications and continuity with pedal arch. Whereas angiography selected the best suitable runoff vessels in 32 cases, colour Doppler sonography proved to be correct in all patients at surgical intervention[61]. In 1998 Ligush et al[16] reported equivalent results for Doppler imaging and angiography to guide infrainguinal reconstructions in 36 patients with critical ischaemia.…”
mentioning
confidence: 95%
“…50 For these preoperative examinations, flow and velocities are often very low indeed. High-frequency transducers are required using low colour and spectral pulse repetition settings.…”
Section: Aorto-iliac and Femoropopliteal Segmentsmentioning
confidence: 99%
“…Some centers have reported excellent results with preoperative duplex ultrasonography either as a stand-alone imaging modality 52,53 or as an adjunct to contrast arteriography, in which duplex imaging can identify areas of significant stenosis limiting the contrast arteriogram to a specific area requiring treatment. In our practice, we prefer DSA in these patients using strategies to limit contrast exposure including the use of nonionic iso-osmolar contrast diluted to 50% strength, using CO 2 for proximal arteries or avoiding aortoiliac imaging altogether.…”
mentioning
confidence: 97%